Analisis Kekuatan Pasangan Bibliografi (Bibliographic Coupling) Dan Ko-Sitasi (Co-Citation) Pada Malaysian Journal Of Library And Information Science Tahun 2010-2011 - Sry Junisti Bangun (Jurnal Pustaka Nusantara dan Budaya, 2013)
The purpose of this research was to find how much percentage of coupling bibliographic strength and co-citation in  Malaysian Journal of Library and Information Science 2010-2011. The method used is descriptive method. Author determined that serve as the unit of analysis is the entire scientific articles that found in Malaysian Journal of Library and Information Science publish 2010-2011 volumes 15-16 as much as 52 articles with 1.641 as reference. Bibliographic coupling that articles volume 15, published in 2010 as many as 24 articles, and the co-citation is an article published in 2011 volume 16 as many as 28 articles. The result showed the percentage of bibliographic coupling recapitulation is at 2.67% and the percentage of co-citation recapitulation is at 1.46%. According to results of the research that bibliographic coupling and co-citation in  Malaysian Journal of Library and Information Science publishing year 2010-2011 Volume 15-16 were included low. This suggests that the author of the articles does not use the same subject related to support his writing.